REDESAIN KANTOR IMIGRASI KELAS I TPI SAMARINDA PENEKANAN PADA ORGANISASI RUANG DAN GAYA ARSITEKTUR NEO VERNAKULAR - Waluyo, Paramita; Hidayati, Zakiah; Putra, Hatta Musthafa Adham; Anugerah , Chandra Dwi (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2024)
The Class I Immigration Office of TPI Samarinda is one of the technical implementation units of the regional office of the Ministry of Law and Human Rights of East Kalimantan. It has the duty to carry out some of the main tasks and functions of the Ministry of Law and Human Rights, namely providing travel documents and residence permits for both Indonesian citizens and foreigners, particularly in the areas of Samarinda city, Bontang, Kutai district, and Mahakam Ulu. As a public service office, the Immigration Office faces several challenges, including poorly planned spatial organization, lack of adequate photo studios, separate service areas, and unplanned space additions, all of which hinder the primary activities and functions within the office. The redesign of the Class I Immigration Office of TPI Samarinda emphasizes spatial organization and incorporates the architectural style of Neo Vernacular Dayak Kenyah. This emphasis aims to facilitate both visitors and employees in carrying out activities within the office through the application of a grid spatial organization. The application of the Neo Vernacular Dayak Kenyah architectural style includes the form, facade, and building ornaments.